Climax of the ages studies in the prophecy of Daniel - Tatford, Frederick Albert, 1901- (London, UK Marshall, Morgan and Scott, 1953)
Includes bibliographical references and indexes.
Brethren writer.
Keywords: Bible. O.T. Daniel, apocalyptic passages -- commentaries